Isolation and Activity Assay of Secondary Metabolites of Aspergillus niger in-Habiting in Termite’s Queen Nest Macrotermes gilvus Hagen., on Enriched Media - Yohannes Alen; Evi Guslianti; Netty Suharti (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
The Fungus is a group of the microorganisms that produce secondary metabolites. Secondary metabolites of fungus may be changed in different media. Secondary metabolites from Aspergillus niger in habiting in termite’s queen nest Macrotermes gilvus Hagen are disappeared gradually in artificial media. It was the reason to enrich the media with termite’s queen nest. The purpose of this research was to obtain the similar secondary metabolites of Aspergillus niger as it grows in their habitat. Enrichment was done with the experimental method. It used three concentrations of nest 0.25; 0.75 and 1 g/mL Sabouraud Dextrose Agar (SDA) media. Isolation was done use chromatography method. The antibiotic activities against Pseudomonas aeruginosa ATCC 27853 and Enterococcus faecalis ATCC 10541 were performed by the diffusion method. Results showed that enrichment of nest 1 g/mL media gave the best growth of fungus and it obtain the similar secondary metabolites as it grows in their habitat. Three pure compounds, EG-13-31-2, EG-13-34-9, and EG-13-44-2 were obtained. Based on physicochemical data, all compounds were terpenoid class and one of them (EG-13-34-9) contain the phenolic group. All compounds have activity against Pseudomonas aeruginosa ATCC 27853 and Enterococcus faecalis ATCC 10541 the bacteriostatic category.Key words: Aspergillus niger; Macrotermes gilvus Hagen; Sabouraud Dextrose Agar (SDA); Isolation; Enrich Media; Diffusion Method